Využití finanční analýzy v podniku - Kalousková, Jarmila (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce je zaměřena na posouzení finanční situace společnosti PIKE ELECTRONIC, spol. s r.o. pomocí elementárních metod finanční analýzy. Kromě klasické roční finanční analýzy byla aplikována také měsíční finanční analýza. Na základě podkladů z provedené finanční analýzy byly odhaleny příčiny finanční situace podniku a navržena vhodná opatření k nápravě popř. k udržení stavu. Součástí práce je také přiblížení základních přístupů k finanční analýze a zhodnocení finanční analýzy doposud prováděné v podniku, odhalení jejích nedostatků a doporučení, jak finanční analýzu nadále provádět a efektivně využívat v podnikovém a finančním řízení.

Diploma thesis is focused on the examination of financial standing of the PIKE ELECTRONIC, spol. s r.o. company with the usage of elementary methods of financial analysis. In addition to classic annual financial analysis was executed also monthly financial analysis. On the base of the details arisen from the performed financial analysis the factors of the company financial standing were discovered and appropriate improving arrangements were specified. The thesis also contains clarification of basic approaches to financial analysis and evaluation of financial analysis which have been performed in the company till this time, detection of their deficiencies and the recomendation how to perform finacial analysis in future period including the way of using it in business and financial management.
Application of Financial Analysis in a Company
Keywords: Finanční analýza; přístupy k finanční analýze; elementární metody; měsíční finanční analýza; Financial analysis; approaches to financial analysis; elementary methods; monthly financial analysis